Pengaruh Kecerdasan Emosional Terhadap Perilaku Sosial Siswa Di SMP Lokon St. Nikolaus Tomohon - Muharli Mua, Marianus; Magdalena Tangkilisa, Dewi Felisia; Bisala, Margaretha; Lovearthus Paat, Glorius (Universitas Pakuan, 2025)
THE INFLUENCE OF EMOTIONAL INTELLIGENCE ON STUDENTS' SOCIAL BEHAVIOR AT LOKON ST. NIKOLAUS JUNIOR HIGH SCHOOL, TOMOHONThis study aims to determine the level of emotional intelligence and social behavior of students and to analyze the influence of emotional intelligence on social behavior of students at Lokon St. Nikolaus Middle School, Tomohon. This study used a quantitative method, with students at Lokon St. Nikolaus Middle School, Tomohon, as respondents. Data were obtained by distributing questionnaires to respondents. Respondents were determined using the Slovin formula, resulting in 150 respondents from a population of 239 at Lokon St. Nikolaus Middle School, Tomohon. Based on the results of the normality test table, it can be concluded that the results obtained using the One-Sample Kolmogorov-Smirnov Test with the assistance of IBM SPSS 25 are normally distributed with a significance value of 0.078 0.05. Furthermore, the linearity test results showed an F-value of 1.523 with a significance value of 0.057 0.05, indicating a linear relationship between the independent and dependent variables. The results of the study indicate that emotional intelligence has a calculated coefficient of 0.81, categorized as very good, while students' social behavior has a calculated coefficient of 0.82, categorized as very good. Through simple regression analysis, it can be concluded that emotional intelligence influences students' social behavior at Lokon St. Nikolaus Middle School, Tomohon, with a coefficient of determination of 0.604. Based on the results obtained, the coefficient interval is categorized as strong, with a percentage of 60.4% of emotional intelligence influencing students' social behavior, while 39.6% is influenced by other factors.